Active Case Detection of Rifampicin Sensitive and Resistant Tuberculosis by Systematic Screening among Household Contacts of Rifampicin-Resistant Tuberculosis Patients in Dhaka, Bangladesh - Sharaque, Azizur Rahman; Rahman, K M Thouhidur; Rayna, Shahrin Emdad; Sultana, Marzan; Daru, Paul; Banu, Sayera; Islam, Syed Shariful; Khalequzzaman, Md (Scripta Medica, 2024)
Background/Aim: Patients with rifampicin resistant-tuberculosis (RR-TB) may remain a source of infection for longer than patients with rifampicin sensitive-tuberculosis (RS-TB). This study aimed to detect active cases of RS-TB and RR-TB through systematic screening among household contacts of RR-TB patients in Dhaka, BangladeshMethods: This cross-sectional study was conducted among the 355 household contacts (HHCs) of 93 RR-TB primary cases identified from various centres in Dhaka, diagnosed between November 2020 and October 2021. For the identification of active cases of tuberculosis (TB), systematic screening among HHCs was done, where verbal screening was performed to check the presence of symptoms of TB. Those who had at least one symptoms of TB were considered as symptomatic contacts. Later GeneXpert analysis of sputum was done among the screened symptomatic contacts. Data was collected using a pretested, semi-structured, interviewer-administered questionnaire. Results: An estimated 30.4% of respondents were ≤15 years of age. TB-like symptoms were prevalent among 9.9% of respondents. Loss of appetite (45.7%), unexplained weight loss (40.0%) and cough (37.1%) were the most common symptoms. Among the contacts with TB-like symptoms, 6.7% were diagnosed as a case of TB (3.35% were RR-TB, and 3.35% were RS-TB). The number needed to be screened to find an active case of TB was established at 178 among the HHCs of RR-TB.Conclusions: About one in ten RR-TB HHCs showed TB-like symptoms. One in fifteen HHCs with TB-like symptoms was an active case of TB. Regular, effective screening of RR-TB contacts is needed to stop the transmission.
Keywords: Tuberculosis; Bangladesh; Drug-resistant tuberculosis; Rifampicin; Close-contact transmission